2021
DOI: 10.3389/fmicb.2021.698586
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Germination Dynamics of Plasmopara viticola Oospores Highlights the Presence of Phenotypic Synchrony With the Host

Abstract: The plant disease onset is a complex event that occurs when the pathogen and the host encounter in a favorable environment. While the plant–pathogen interaction has been much investigated, little attention has been given to the phenological synchrony of the event, especially when both plant and pathogen overwinter, as in the case of grapevines and the downy mildew agent, the oomycete Plasmopara viticola. Oospores allow this obligate parasite to survive grapevine dormancy and, germinating, produce inoculum for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Interestingly, in correspondence with the infection risk indicated by the EPI model, the oospores showed a reduction in t (with minimum values ranging from two to five days). This confirms that t significantly decreases when the plant reaches susceptibility to P. viticola (Maddalena et al, 2021). It must be point out that, since the oospores are the only overwintering structures of the pathogen and the source of the vital inoculum for primary infection, obtaining real biological data on oospore germination is particularly important also from an epidemiological point of view since it provides information on the availability of inoculum for primary infections.…”
Section: Oospore Germination Dynamicssupporting
confidence: 68%
See 3 more Smart Citations
“…Interestingly, in correspondence with the infection risk indicated by the EPI model, the oospores showed a reduction in t (with minimum values ranging from two to five days). This confirms that t significantly decreases when the plant reaches susceptibility to P. viticola (Maddalena et al, 2021). It must be point out that, since the oospores are the only overwintering structures of the pathogen and the source of the vital inoculum for primary infection, obtaining real biological data on oospore germination is particularly important also from an epidemiological point of view since it provides information on the availability of inoculum for primary infections.…”
Section: Oospore Germination Dynamicssupporting
confidence: 68%
“…Relating the influence of environmental conditions to the germination dynamics could provide indication on inoculum availability for primary infections and the need for a fungicide treatment. A recent study demonstrated that the number of days required by the oospores to germinate (t) decreases when grapevine reaches susceptibility to P. viticola (Maddalena et al, 2021). The promising results obtained in the previous years led the authors to evaluate the effectiveness of EPI model extending its use in other viticultural area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed model for primary infection warning starts when the grapevine shoots are in stage 13 of the BBCH scale (i.e., the shoots are at least 10 cm long, or a few unrolled leaves) at minimum [30]. Then, the average daily air temperature, precipitation, wind, and daytime/nighttime are monitored.…”
Section: Warning System Algorithm and Model Overviewmentioning
confidence: 99%